STUDY ON THE DYNAMIC CHARACTERISTICS OF A SYSTEM WITH A LOOSE-RUBBING COUPLED FAULTY ROTOR (MT) - FU YongBing (Jixie qiangdu, 2023)
A dynamic model of rotor system with loosening and rubbing multiple faults coupling was established. Fourth-order Runge-Kutta method was used for numerical simulation. Periodic bifurcation diagram of rotor system, maximum rub-impact force diagram, amplitude diagram of loose bearing support, phase diagram as well as Poincaré map of the rotor system were obtained. The analysis was focused on the influence of loose mass on the dynamic characteristics of the system.The research shows that the looseness fault makes the rotor system enter the rub-impact motion at low speed. The rotational speed range of subharmonic motion, almost periodic motion and chaotic motion increases. At the same time, the corresponding maximum friction force and loose support amplitude are larger. The large loose mass can reduce the vibration amplitude of the loose bearing support. At the same time, it can make the system in the periodic motion without rub-impact in the long range of low speed, which is conducive to the stable state of the system under fault conditions.